Analisis Minat Mahasiswa dalam Berinvestasi Saham di Pasar Modal - Rahayu, Eva Putri; Khoirudin, Rifki (Jurnal Samudra Ekonomi dan Bisnis, 2023)
The study aims to determine whether investment motivation, investment knowledge and understanding, minimum investment capital, investment benefits, and perceptions of investment risk, affect students' interest in investing in stocks in the capital market. The research population is Ahmad Dahlan University students. The sample used a purposive sampling method, namely 395 samples. Multiple regression analysis tools are used to determine the relationship between the independent variables and the dependent variable. The results of the study show that only investment motivation has a positive and significant influence on students' interest in investing in stocks in the capital market. Meanwhile, four other independent variables, namely investment knowledge and understanding, minimum investment capital, investment benefits, and perceptions of investment risk, were found to have no significant effect on students' interest in investing in stocks in the capital market.